Analysis of Image–Text Relationships for Developing a Holistic Rubric in Digital Comic Creation - Vira Rahmawati; Rizki Hikmawan (UNDIKMA, 2026)
The development of digital media has shaped Generation Alpha’s reading characteristics to be more visual and multimodal, requiring more effective and adaptive digital comic design. This study aims to analyze the configuration of image–text relationships in digital comics and to develop a holistic assessment rubric. A qualitative descriptive-analytical approach was employed, involving the analysis of 100 popular digital comics and interviews with 30 Generation Alpha readers. Data were analyzed using thematic analysis and conceptual mapping to identify patterns of multimodal humor and reader preferences. The results indicate that comics with strong visual–verbal integration, coherent narrative flow, concise text, and social relevance have the highest preference levels, while one humor configuration received no preference (0%). This finding indicates that not all multimodal humor strategies equally resonate with Generation Alpha readers, highlighting the importance of aligning visual–verbal design with learners’ cognitive and cultural characteristics. In addition, four contextual image–text relational configurations were identified in constructing meaning and humor. The primary contribution of this study is the development of a five-aspect holistic rubric for evaluating educational multimodal digital comics. This rubric provides an initial conceptual framework for designing and assessing digital comics in educational contexts and may assist teachers, instructional designers, and digital media developers in creating more engaging and pedagogically relevant learning media. Further studies are required to examine its validity and reliability across broader educational settings.